Pengaruh Kompensasi, Motivasi dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan pada PT. Gujati 59 Utama sukoharjo - Armitasari, Hera, Basworo Dibyo, SE, M.Si (2016)
Job satisfaction is a reflection of one's job is the impact of the positive attitude of employees towards work and everything that is faced in their work environment. Kompesasi, motivation and work environment is believed to be capable of influencing employee satisfaction in achieving the goals set. The purpose of this study was to determine whether the compensation, motivation and work environment directly significant effect on employee job satisfaction. The population in this study are employees of PT. GujatiSukoharjo Top 59 totaling 55 respondents. Data used by the questionnaire technique. Data analysis technique used is Bergandadengan Linear Regression Analysis using SPSS 21.0 for windows. Based on the analysis proved that compensation, motivation and work environment positive and significant impact directly on job satisfaction of employees at PT. Gujati Top 59 Sukoharjo. The implications of this research, employee job, Compensation, motivation ang The work environment must be improved.